Critical issues encountered in the analysis of protein-phenolic binding interactions via fluorescence spectroscopy. (March 2022) - Condict, Lloyd; Kasapis, Stefan
Abstract: There is a substantial volume of research articles in the field of protein-ligand interactions, with a large proportion using inappropriate methodology for the fluorescence spectroscopy analysis of binding interactions. The most common issues being overlooked are the inner filter effect and the use of unsuitable equations to calculate binding strength and stoichiometry, leading to the propagation of questionable methodology and reported results throughout multiple fields. In this communication, we carefully explain these issues and approaches to overcome them, including accounting for the inner filter effect, the use of appropriate equations to obtain dissociation constant ( K d ) values (as opposed to the commonly misused Stern-Volmer equation), and carefully dealing with binding stoichiometry using the Job plot (often misjudged using the Hill coefficient instead). We hope that the work will bring attention to critical and often common issues in fluorescence spectroscopy, as well as improving the approaches used in the binding analysis of protein-ligand systems. Thus, it should provide a good example of how to go about this type of research, as well as being of interest to the broad readership of the journal. Graphical abstract: Image 1 Highlights: Errors in fluorescent quenching of food protein-phenolic complexes are discussed. Filter effects are commonly overlooked as a contributor to quenching. Inappropriate (linear) equations are often used to determine binding constants. Binding stoichiometry often (incorrectly) determined using the Hill coefficient.